2015
DOI: 10.1016/j.reffit.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Induced polarization effect in reservoir rocks and its modeling based on generalized effective-medium theory

Abstract: One of the major tasks of the petroleum resource-efficient technologies (pREFFIT) is the development and improvement of the methods of exploration for energy resources. This review paper summarizes the results of the research on induced polarization (IP) effect in reservoir rocks conducted by the University of Utah Consortium for Electromagnetic Modeling and Inversion (CEMI) and TechnoImaging. The electrical IP effect in hydrocarbon (HC) bearing reservoir rocks having nonmetallic minerals is usually associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…5c. Burtman and Zhdanov (2015) observed that the relaxation time for a spheroid metallic grain is proportional to its major axis when it aligns with the electric field, and our findings suggest that the network structure of massive sulfides may serve a similar role. Since T is proportional to a 2 , T remains unchanged with the same-sized particles clustered together.…”
Section: Specifying General Trends and Geometric Influences On Charge...supporting
confidence: 58%
“…5c. Burtman and Zhdanov (2015) observed that the relaxation time for a spheroid metallic grain is proportional to its major axis when it aligns with the electric field, and our findings suggest that the network structure of massive sulfides may serve a similar role. Since T is proportional to a 2 , T remains unchanged with the same-sized particles clustered together.…”
Section: Specifying General Trends and Geometric Influences On Charge...supporting
confidence: 58%
“…Revil et al [10,11] used a new model to study the influence of oil saturation of formation water on the complex resistivity of oil-bearing sandstone and found that the resistivity and the amplitude of the phase increase with increasing oil saturation, while the imaginary component of the complex resistivity decreases. Burtman and Zhdanov [12] found that oil-bearing sandstone and carbonate rocks have significant induced polarization response characteristics through experiments and verified the early geophysical application of the IP method in oil-bearing reservoir exploration. By measuring the complex resistivity of artificial sandstone with different physical properties under different water saturation conditions and by fitting the data using the Cole-Cole model, Jiang et al [13] found that the frequency index in the model initially decreased and then increased with decreasing water saturation, so they pointed out that it is expected that this index is expected to be applied in the study of oil-water distribution in reservoirs.…”
Section: Introductionmentioning
confidence: 73%
“…When pores expand, electrolytic solution gradually fills the pores, and the corresponding capacitance increases. In addition, Burtman et al analyzed the induced polarization mechanism of rocks and tested the IP response of sandstone, and found that the electric double layer is related to the size and shape of pores filled with electrolyte [13]. Compared with the discrete phenomenon in the third chapter, there is a certain regularity in creep electrochemical test, that is, with the development of creep deformation of rock samples, it shows a decreasing trend.…”
Section: Change Law Of Electrochemical Impedance Spectroscopy In Creep Process Of Corroded Sandstonementioning
confidence: 99%